How far is China from hitting its climate targets? An overview of China's energy sector - Juuso Kaaresvirta; Eeva Kerola; Riikka Nuutilainen; Seija Parviainen; Laura Solanko (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
China is by far the world's largest consumer of primary energy. Its vast energy demands are a leading issue for global energy use, driving pollution trends and prices on commodity markets. Despite huge increases in non-fossil capacity from nuclear and renewables, China still burns tremendous amounts of coal to meet its primary energy needs. Domestic energy consumption has risen faster than energy production, and thereby increased China's dependence on energy imports. China is the world's largest polluter, so any effort on the country's part towards cleaner energy has major implications for global decarbonisation efforts. This overview comprises ten briefs on China's energy sector. They cover recent developments in energy use and the shifting dynamics in primary power generation aimed at meeting China's energy needs.
urn:nbn:fi:bof-202102161116
Keywords: 330; China; energy; oil; natural gas; coal; electricity; renewable energy; production; investment; foreign trade; emissions